Effect of Date Palm Pollen Grains (Phonenix Ductylifera) on Testes Function and Fertility in Rats - Arrak, J.K. (The Iraqi Journal of Veterinary Medicine, 2010)
This study presents the effects of Date Palm Pollen grains (DPP) (phoenix ductylifera) on testes function, fertility and pregnancy index in male adult rats.Forty adult male albino rats were divided randomly into four equal groups .The first group was not received DPP and considered as control group and the other groups (T1, T2 and T3) were received daily gavages of aqueous suspension(DPP) containing 30, 60 and 120 mg/kg B.W for 56 days. At the end of experiment blood were collected to determine serum testosterone level. Sexual reaction was determined and reproductive indices (fertility, pregnancy) index were examined in normal fertile 32 female rats mated with treated male rats. Sperm concentration, mortality and morphology of treated groups were, also determined. The results showed that treatment with DPP for 56days led to significant (P<0.05) increase in serum testosterone concentration, testicular weights, mortality and sperm concentration in (T2 and T3) groups compared with control and T1 groups, but sperm morphology, concentration was significantly decrease in the T2 +T3 groups compared with control and T1 groups. Also,treatment with DPP cause significant (P≤0.05) increase in fertility and pregnancy index for all treated groups, as compared with control group, furthermore, sexual reaction was significantly (P≤0.05) decrease in the 3 treated groups compared with control group. conclusion, DPP suspension plays a role in improvement sperm quality and enhances fertility in adult rats.